Fading corporate survival prospects: Impact of co‐selection bias in resource allocation on strategic intent - Burgelman, Robert A.; Aaltonen, Pertti (Strategic Management Journal, 2024)
Abstract Research Summary Our field study of new business development in a German‐based global pharmaceutical company reveals that the emergence of co‐selection bias in project‐level stage‐gate resource allocation engendered a corporate‐level innovation portfolio imbalance. We show how the corporate portfolio imbalance resulted from incoherent managerial activities in the multilevel resource allocation process (RAP) decision context and how this caused fizzling out of the proactively established incipient strategic context of the favored‐for‐growth business unit. Moreover, we identify strategic RAP exploitation challenges that explain why sequential exploitation capability and exploitation drive deficits caused an exploitation trap that limited strategic discretion and stymied top management strategic intent to maintain the company's independence. Our integrated frameworks augment strategic management theory of corporate RAP and offer guidance for future research. Managerial Summary We draw attention to the little‐noticed phenomenon of co‐selection bias emerging in the project‐level stage‐gate resource allocation to new business development and maladaptive corporate‐level innovation portfolio outcomes that it may produce. We show how top management can use the Bower–Burgelman RAP model to analyze the multilevel RAP decision context and identify the forces that may engender out‐of‐context managerial agency, such as co‐selection bias. We highlight strategic RAP exploitation challenges that top management must meet by matching the RAP exploitation drive with a commensurate RAP exploitation capability to avoid an exploitation trap, thereby increasing the chances of company survival.